Molecular and phenotypic analysis of mutations causing anionic phospholipid deficiency in closely related yeast species - Batová, M; Dzugasová, V; Borecká, S; Goffa, E; Oblasová, Z; Subík, J (Folia microbiologica, 2009)
The pel1 mutation in Saccharomyces cerevisiae and the Cgpgs1Delta mutation in Candida glabrata result in deficiency of mitochondrial phosphatidylglycerolphosphate synthase and lack of two anionic phospholipids, phosphatidylglycerol and cardiolipin. DNA sequence analysis of the PCR-amplified pel1 mutant allele revealed that the pel1 mutation resulted from a single amino-acid substitution (Glu(463)Lys) in the C-terminal part of encoded enzyme. The CgPGS1 gene cloned in a centromeric pFL38 vector functionally complemented the pel1 mutation in S. cerevisiae. Likewise, the ScPGS1 gene cloned in pCgACU5 plasmid fully complemented the Cgpgs1Delta mutation in C. glabrata. This mutation increased the cell surface hydrophobicity and decreased biofilm formation. These results support a close evolutionary relatedness of S. cerevisiae and C. glabrata and point to the relationship between expression of virulence factors and anionic phospholipid deficiency in pathogenic C. glabrata.
Keywords: Hydrophobic and Hydrophilic Interactions; fenotyp; Phenotype; mutace; hydrofobní a hydrofilní interakce; Fungal Proteins; molekulární sekvence - údaje; Amino Acid Sequence; kvasinky; sekvenční seřazení; Transferases (Other Substituted Phosphate Groups); transferasy pro jiné substituované fosfátové skupiny; Phospholipids; Biofilms; fosfolipidy; sekvence aminokyselin; Molecular Sequence Data; biofilmy; Mutation; Yeasts; fungální proteiny; Sequence Alignment